A influência da resistência de terra nos efeitos das descargas atmosféricas - Santos, Camila Guesine dos (2009)
There is great concern by the power systems utilities related to disturbances that generate induced overvoltages in the power network, as they reach the consumer sensitive equipment, causing damage and losses. In consequence of this framework, the power systems utilities get large financial losses every year due to indemnity for damage to such equipments. Among the disturbances that lead to induced overvoltages are lightning. Thus, in this work it was developed the study and analysis of the lightning´s effect on loads allocated on average (11kV/15kV) and low voltage (below 600V) under the influence caused by the resistance of grounding. For modeling and simulation of the system under analysis, the program for transient study ATP (Alternative Transient Program) was used. To develop the study, it was designed a system comprising of an 88kV transmission line, a substation, a distribution line of 13.8 kV and loads representing residential consumers. It was also analyzed the use of surge suppressor in the low voltage distribution transformers as a way to mitigate the induced overvoltages that reach consumers.